A type of dissoluble organosilicon elastomer with stretchable, self-healable and antibacterial properties. (April 2021) - Zhang, Kaiming; Gao, Chuanhui; Song, Jingyao; Song, Chengxin; Wang, Zhe; Wu, Yumin; Liu, Yuetao; Sun, Jiawen
Abstract: Bacterial resistance to antibiotics reduced the demand for antibiotics in the field of medical devices. Polymer antibacterial materials have shown great potential in the medical field. However, the treatment of materials after use is not environmentally friendly. Therefore, the development of dissoluble polymer antibacterial materials has become an urgent challenge. In this paper, an antibacterial polymer material with high self-healing ability and rapid dissolution is reported. The new material was formed by the Schiff base reaction and cross-linking of aldehyde group and amino in terephthalaldehyd (TA), 3, 4-diaminofurazan (DAF) and α, ω-aminopropyl terminated polydimethylsiloxane (PDMS, Mn = 3000). The properties of the material were further enhanced by the coordination of zinc ion with nitrogen and oxygen atoms of 3, 4-diaminofurazan. The antibacterial polymer material designed by us can be effectively repaired at 100 °C. The first repair efficiency was 89.5%. After repeated repair, its mechanical properties were not significantly reduced. E. coli and S.aureus were used to evaluate the antibacterial ability of the material. The antibacterial efficiency of the material was 99.9993% and 99.9997% respectively. This new idea solved the urgent problems in the current application, and provided guidance for the research of flexible antibacterial materials. Graphical abstract: Image 1 Highlights: PDMS with low molecular weight makes polymers have more crosslinking sites. Elastomer has good mechanical properties and fatigue resistance. Elastomer can be rapidly dissolved by the dynamic exchange reaction. Elastomer has excellent antibacterial ability.